Tolerance and short term efficacy of rituximab in 43 patients with systemic autoimmune diseases. Issue 6 (18th November 2004) - Gottenberg, J-E; Guillevin, L; Lambotte, O; Combe, B; Allanore, Y; Cantagrel, A; Larroche, C; Soubrier, M; Bouillet, L; Dougados, M; Fain, O; Farge, D; et al.
Abstract : Objective: To assess the tolerance and efficacy of rituximab in patients with various autoimmune diseases seen in daily rheumatological practice. Methods: 866 rheumatology and internal medicine practitioners were contacted by email to obtain the files of patients treated with rituximab for systemic autoimmune diseases. Patients with lymphoma were analysed if the evolution of the autoimmune disease could be evaluated. Results: In all, 43 of 49 cases could be analysed, including 14 with rheumatoid arthritis (RA), 13 with systemic lupus erythematosus (SLE), six with primary Sjögren's syndrome (pSS), five with systemic vasculitis, and five with other autoimmune diseases. Rituximab was prescribed for lymphoma in two patients with RA and two with pSS. In the 39 other cases, rituximab was given because of the refractory character of the autoimmune disease. The mean follow up period was 8.3 months (range 2 to 26). There were 11 adverse events in 10 patients and treatment had to be discontinued in six. Efficacy was observed in 30 patients (70%): RA 11, SLE 9, pSS 5, vasculitis 2, antisynthetase syndromes 2, sarcoidosis 1. The mean decrease in corticosteroid intake was 9.5 mg/d (range 0 to 50) in responders. Seven patients experienced relapse after mean 8.1 months (5 to 15). Three patients died because of refractory autoimmune disease. Conclusions: Despite absence of marketing authorisation, rituximab is used to treat various refractory autoimmune diseases in daily rheumatological practice. This study showed good tolerance and short term clinical efficacy, with marked corticosteroid reduction in patients with SLE, pSS, vasculitis, and polymyositis.